(untitled) - Quaschning, Volker (London, 2005)
Beginning with an overview of renewables (including biomass, hydroelectricity, geothermal, tidal, wind, and solar power) this book explores the fundamentals of various renewable energy systems. The main focus is on technologies with high development potential such as solar thermal systems, photovoltaics, and wind power. This text not only describes technological aspects but also deals consciously with problems of the energy industry. In this way, the topics are treated in a holistic manner, enabling readers to gain a broad understanding of renewable energy technology and its potential.
Keywords: Năng lượng tái tạo,Renewable energy sources